The problem of information security in the development of the information society - Torichniy , Vadym (Theory and Practice of Public Administration, 2019)
In modern conditions, information is without exaggeration one of the decisive resources for the development of civilization. Information security in the modern world actively influences all spheres of life of both individual societies and states, and the entire world community. The purpose of the article. Based on the foregoing, the purpose of our research is the need for a state management analysis of the role of information security in the development of the information society in the context of the globalization challenges of our time. The presentation of the main material. Speaking about the content and structure of information security, it should be borne in mind that the category «information security» at this stage may have different content when used in different contexts. Thus, two trends emerged in government bodies in defining the concept and structure of information security. Humanitarian representatives associate information security only with the institution of secrecy. Representatives of law enforcement agencies offer to extend the scope of information security to almost all issues and relations in the information sphere, in fact, identifying information security with the information sphere. In our opinion, both points of view represent extreme positions. In the modern world there is an intensive build-up of information and communication potential, information globalization contributes to integration processes in all other spheres. The means for this are the development of communications, the use of outer space for the transmission of information, the growth of global information networks, the computerization of many processes of human activity. Findings. Thus, it can be said that the point of view that information security is a state of society that provides reliable and comprehensive protection of an individual, society and the state from the impact of a special type of threats, acting in the form of organized or spontaneous information flows carried out in the interests of regressive, reactionary or extremist-minded political and social forces and aimed at the conscious deformation of the public individual and individual consciousness. It is obvious that an effective state policy in the information sphere, including in the aspect of information security, largely depends on the correct choice of priorities in scientific research of these problems, on the development of adequate scientific models and approaches to their solution.